ANALISIS KUANTIFIKASI AIR DAN DAYA DUKUNG LINGKUNGAN UNTUK PENGEMBANGAN TAMBAK DI KAWASAN MINAPOLITAN KABUPATEN PINRANG - Asbar, Asbar; Fattah, Hattah; Putra, Firmansyah (Torani Journal of Fisheries and Marine Science, 2015)
This study aims to: (1) Determine the biophysical characteristics of the waters for aquaculture development, (2)analyzing the quantity of water available for aquaculture development, and (3) to analyze the ability of carryngcapacity waters to support the development of aquaculture in the region Minapolitan in Pinrang. Observations andfield data collection in location of sampling points recorded by means of its geographical position positioning(GPS). The method of analysis using the waters of the pond carryng capacity analysis which includes quantificationof water at high tide and low tide and quantification of aquaculture waste. The results of this study showed thatbased on the availability of water at the beach for the cultivation of shrimp and fish ponds which could be loadedwith water from the shore to the cultivation of shrimp and fish with a height of 70 cm water ha-1 that is widelyapplied in traditional farms with the availability of water at the beach for Village area of 450.68 ha Lotang Salo,Wiringtasi Village area of 955.49 ha, and the Village area of 512.91 ha Tasiwalie. While the water level of 1 m insemi-intensive pond applications and intensive with the availability of water at the beach to the village area of315.47 ha Lotang salo, covering an area of 668.84 ha Wiringtasi village, and the village area of 359.04 haTasiwalie. Suggestions of this study is the allocation of land use and cultivation of Akua - input must be adjusted tothe carrying capacity and the feasibility bioteknis, For coastal environmental sustainability is maintained, then theamount of organic waste from aquaculture activities are discharged into coastal waters should be no more than 798kg for Tasiwalie village and 756 kg for the Village Wiringtasi.Keywords: Quantification of water, pond marginal, carryng capacity